Results of the salmon fishery season in Kamchatka Region in 2023 - A. V. Bugaev; О. V. Zikunova; N. B. Artyukhina; S. V. Shubkin (Известия ТИНРО, 2024)
Results of salmon fishery in Kamchatka Region in 2023 are overviewed. Data of fishery statistics on catches of pacific salmon are presented, by fishing districts. Feasibility of fishery forecasts is estimated. Seasonal dynamics of landing is shown for the main stocks of five salmon species. The spawning stocks on the eastern and western coasts of Kamchatka are assessed.